Temporal trends of migraine and tension-type headache burden across the BRICS: implications from the Global Burden of Disease study 2019 - Zhang, Yuan-jie; Li, Xin-yu; Guo, Zhi-lin (Frontiers in Neurology, 2023)
Background: Headache disorders have become a significant global public health issue, with a notably high prevalence observed in developing countries. However, few studies have assessed headache disorders trends in Brazil, Russia, India, China and South Africa (BRICS). This study aimed to assess the prevalence of headache disorders in individuals across the BRICS, spanning the years 1990 to 2019.We obtained headache disorders data from the Global Burden of Disease 2019 study (GBD2019). This evaluation examined incidence rates, prevalence, and disability-adjusted life-years (DALYs) for migraine and tension-type headache (TTH) across demographic factors like age, gender, year, and country. Migraine and TTH were diagnosed based on the International Classification of Headache Disorders (ICHD-3) criteria. We used disease codes from the International Classification of Diseases, 10th revision to identify migraine and TTH cases. Statistical analyses included calculating age-standardized rates and estimated annual percentage changes.Future disease burden was projected using a log-linear age-period-cohort model.In 2019, India had the highest prevalence of migraine (213890207.93 cases) and TTH (374,453,700 cases). Brazil had the highest migraine age-standardized prevalence rate (18,331 per 100,000) and incidence rate (1,489 per 100,000). For TTH, India had the highest prevalence (26,160 per 100,000) while Russia had the highest incidence (11,512 per 100,000). From 1990 to 2019, China showed the greatest increase in migraine and TTH prevalence. India had the highest migraine (7,687,692) and TTH (741,392) DALYs in 2019.Migraine and TTH remain highly prevalent in BRICS nations, inflicting considerable disability burden. While India and China face mounting disease prevalence, Brazil contends with high incidence rates. Tailored interventions based on country-specific epidemiological profiles are warranted to mitigate the public health impact.